Demographic change and public sector budgets in a federal system - Michael Hofmann; Gerhard Kempkes; Helmut Seitz (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper examines the effects of demographic change on public finances in a federal system. We develop a simple methodical procedure to measure the effect of demographic changes on public revenues and expenditures. We apply our method to the local, state and federal government sector as well as on the social security system in Germany. Our results suggest that demographic change will lead to significant vertical fiscal imbalances between the different layers of government. In addition we show, that subnational governments can generate a demographic dividend whereas the social security system and the federal government have to carry an additional burden due to ageing.
Keywords: H11; H68; H77; J11; 330; fiscal federalism; demographic change; sustainability of public finances; Öffentlicher Haushalt; Prognose; Alternde Bevölkerung; Finanzföderalismus; Sozialversicherungsfinanzierung; Deutschland